Bridging Gaps, Building Futures: How DIREKTION Innovates for Global Disaster Resilience - Schlierkamp, Juliane (Proceedings of the International ISCRAM Conference, 2024)
The DIREKTION project, funded under Horizon Europe, aims to revolutionize disaster resilience through advanced technology and collaboration. Addressing the challenges posed by climate change, infrastructure vulnerabilities, and dynamic population densities, it seeks a paradigm shift in emergency responses. By integrating innovative technologies with the practical needs of responders and policymakers, DIREKTION enhances cross-sectoral harmonization and fosters stakeholder communication. Early outputs include drafts of the DIREKTION Assessment and Screening Framework and D-SAT tool, establishing a foundation for future development. The project's presentation at ISCRAM invites valuable feedback and engagement, highlighting its commitment to improving disaster management practices and fostering a more resilient society.